(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Technology is a fast-paced innovation, and people are adapting to it. Record-keeping management plays a crucial role in any organization, and maintaining records today requires investing in technology. This study aimed to determine the effectiveness of new office technologies on record-keeping management, the extent to which the new office technologies help record-keeping management and issues encountered in terms of using new office technologies in the record-keeping management process. The result revealed that the demographic profile of the respondents has a significant record- keeping management process in terms of using new office technology. The extent of new office technology had a factor in the record management process, and the respondents responded effectively. It emphasizes how important it is. However, the respondents encountered issues in terms of use. Therefore, there is a need for improvement and familiarity in using new office technologies to avoid data loss and complexity. The researchers recommend that employers, institutions, and administrations should provide adequate training and schedule training sessions both during and after the introduction of the new technology to help everyone get familiar with it.